(untitled) (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Nepal has felt the adverse impact of climate change even though its contribution to global greenhouse gases (GHGs) is negligible. Many scientists have expressed concern that the general rise in temperatures at high altitudes poses a serious environmental and humanitarian threat in Nepal as many glaciers and glacial lakes are located in the high Himalayas. For this study, I have observed rising temperatures in the Langtang catchment and compared the proportional rise of high altitude and low altitude temperatures as these will have serious implications for glaciers and glacial lakes in the region. As well, conducted a time series observation of water flow and noted that the river flow in the Langtang catchment are decreasing. Given these findings, Nepal may be facing increasing water scarcity while also keeping more serious watch on glacial melt. DOI: http://dx.doi.org/10.3126/hn.v15i0.11289 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 2014, July Page: 30-36